Lipid nanocarrier containing olive oil and olive butter: an approach for bioactive compound delivery systems - da Silva Silveira, Larissa; Zinhani, Mateus Cláudio; da Fonseca, Elisandra da Silva Pena; Fortes, Carolina Rapachi; Rossato, Aline; de Souza Filho, Walter Paixao; Guerim, Pedro Henrique Fortes; Marquezan, Patrícia Kolling; Nunes, Franciane Batista; Santos, Roberto Christ Vianna; Ballus, Cristiano Augusto; Farias, Carla Almeida Andressa; et al. (Disciplinarum Scientia | Naturais e Tecnológicas, 2025)
Olea europaea L., known as the olive tree, belongs to the family Oleaceae and is the only species of this family that produces edible fruits, olives. Olive oil, extracted from these fruits, has been widely used since antiquity due to its antioxidant, moisturizing, and soothing properties, standing out as a promising ingredient in cosmetic and therapeutic industries. However, the incorporation and cutaneous absorption of its antioxidant compounds represent a challenge, since many of them are lipophilic, unstable, and susceptible to degradation by light and oxygen, which limits their use in topical formulations. To overcome such limitations, research and industry have invested in the development of lipid-based nanocarriers, capable of increasing the solubility, stability, and bioavailability of bioactive compounds, while protecting them against hydrolysis and oxidation. This study aimed to prepare a butter containing olive oil and incorporate it, together with the oil itself, into lipid nanocarriers. Stability, biocompatibility, and antimicrobial activity analyses of the obtained systems were performed, in addition to phenolic characterization and evaluation of the antioxidant potential of the oil in its free form. The results demonstrated that olive oil has a high concentration of phenolic compounds, with expressive therapeutic potential. Both the butter and the nanocarriers developed proved to be stable and safe, with no mortality or cell damage, although the nanocarriers did not exhibit antimicrobial activity against the bacterial strains tested. It was concluded that the association between olive oil and lipid nanocarriers is promising for cosmetic applications and topical delivery, offering stability, safety, and functional potential in skin care and protection.